2022
DOI: 10.3390/nu14153165
|View full text |Cite
|
Sign up to set email alerts
|

Omega-9 Modifies Viscoelasticity and Augments Bone Strength and Architecture in a High-Fat Diet-Fed Murine Model

Abstract: The influence of diet on the development of osteoporosis is significant and not fully understood. This study investigated the effect of diets of varying lipid profiles and ω-3, ω-6 and ω-9 composition on the structural and mechanical properties of bone. The hypothesis studied was that a diet high in saturated fat would induce osteoporosis and produce an overall increased detrimental bony response when compared with a diet high in unsaturated ω-6, or ω-9. Male C57BL/6J mice were fed either a control diet, 50:50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 72 publications
(90 reference statements)
0
6
0
Order By: Relevance
“…These beneficial effects on bone metabolism were further confirmed by metabolomic analysis showing a higher concentration of DHA and EPA not only in plasma but also in BM and bone matrix of HFD + F compared to HFD mice, which was associated with a positive impact on bone quality and lower BMA and improved bone microstructural changes. Besides omega-3 PUFAs, omega-6 and omega-9 PUFAs in the diet may benefit bone parameters 20 , 40 . Thus, it is important to pay more attention to the composition of different PUFAs in experimental diets and their beneficial effects on bone.…”
Section: Discussionmentioning
confidence: 99%
“…These beneficial effects on bone metabolism were further confirmed by metabolomic analysis showing a higher concentration of DHA and EPA not only in plasma but also in BM and bone matrix of HFD + F compared to HFD mice, which was associated with a positive impact on bone quality and lower BMA and improved bone microstructural changes. Besides omega-3 PUFAs, omega-6 and omega-9 PUFAs in the diet may benefit bone parameters 20 , 40 . Thus, it is important to pay more attention to the composition of different PUFAs in experimental diets and their beneficial effects on bone.…”
Section: Discussionmentioning
confidence: 99%
“…Each tibia was placed horizontally on support bars positioned 8 mm apart with the anterior bow facing downward as per our previously published protocol. [246,247] Using a universal testing machine (Criterion 43, MTS, Eden Prairie, MN, USA), a vertical force was applied to the tibial mid-shaft using a 3 mm diameter leading roller and a 5 kN load cell. Each tibia was loaded until failure at a displacement rate of 0.02 mm −1 s. As the cross-sectional area of the tibia was non-uniform and similar to other studies, [246,248,249] we assumed the cross-sectional area was circular and obtained the mechanical properties including the stress, 𝜎 (Pa), in Equation ( 1), and elastic modulus, E (Pa), in Equation (2).…”
Section: Methodsmentioning
confidence: 99%
“…[ 246,247 ] Using a universal testing machine (Criterion 43, MTS, Eden Prairie, MN, USA), a vertical force was applied to the tibial mid‐shaft using a 3 mm diameter leading roller and a 5 kN load cell. Each tibia was loaded until failure at a displacement rate of 0.02 mm −1 s. As the cross‐sectional area of the tibia was non‐uniform and similar to other studies, [ 246,248,249 ] we assumed the cross‐sectional area was circular and obtained the mechanical properties including the stress, σ (Pa), in Equation (), and elastic modulus, E (Pa), in Equation (). σ0.33embadbreak=0.33emFLcO4I$$\begin{equation}{{\sigma}}\ = \ \frac{{F*L*{c}_O}}{{4*I}}\end{equation}$$ E0.33embadbreak=0.33emFL3d48I$$\begin{equation}E\ = \ \frac{{F{L}^3}}{{d*48*I}}\end{equation}$$Where F is the applied load (N), L = 0.008 is the span distance between the supports (m), c o is the outer radius of the tibial midshaft (m), which was measured using a caliper (Digital, Cole‐Parmer, IL, US), d is displacement (m), and I is the moment of inertia (m 4 ) calculated using Equation (): I0.33embadbreak=0.33emπ4()co4ci4$$\begin{equation}I\ = \ \frac{\pi }{{4\left( {c_o^4 - c_i^4} \right)}}\end{equation}$$where c i is the inner radius of the tibial midshaft (m).…”
Section: Methodsmentioning
confidence: 99%
“…Deshimaru (2005) conducted in vitro cell experiments testing various FAs and found that only oleic acid, an ω-9 MUFA, has the ability to promote osteoblast differentiation [16]. Omer's team first compared ω-6 and ω-9 FAs on bone regeneration in animal experiments and found that animals fed with ω-9 MUFAs exhibited significant improvements in maintaining bone strength and viscoelastic properties [17]. The authors later suggested that besides promoting bone regeneration, ω-9 MUFAs also have a significant inhibiting effect toward bone loss [18].…”
Section: Introductionmentioning
confidence: 99%